Konstruksi Pandangan Komunitas Dance Cover K-Pop di Bali terhadap Budaya Korea Selatan - Octaviani, Kadek Sindi; Wiranata, I Made Anom; Nugraha, A.A. Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
Abstract This study aims to examine the fans' views on South Korean culture because of the phenomenon of Korean Wave hegemony. The research method used in this study is a qualitative research method with a case study approach. Researchers determine the K-Pop dance cover community in Bali as research sources. This study uses the theory of hegemony proposed by Gramsci and the construction of identity from the perspective of cultural studies by Barker. Based on the results of interviews conducted with informants, it was found a fact that the phenomenon of the hegemony of the Korean Wave, especially K-Pop, had a significant impact on the views and lives of fans. The influence caused by the spread of the Korean Wave has helped to build a positive image and view of fans towards South Korea through their success in popularizing their culture abroad. Keywords: hegemony, identity construction, Korean Wave, South Korea